PENINGKATAN KOMPETENSI GURU DALAM MENGEMBANGKAN RPP KURIKULUM 2013 REVISI 2017 MELALUI PENDAMPINGAN BERKELANJUTAN - ENI RINDARTI (Jurnal Pendidikan Islam, 2018)
This study aims to improve the competence of teachers in developing the implementation plan of learning (RPP) on Curriculum 2013 through “Accompaniment of sustained”. The research is conducted for 4 months from Juli to October 2017. The result showed that with the Accompaniment of sustained, the competence of teachers in developing the RPP Curriculum 2013 revision 2017 has increased from the initial conditions to cycle I and cycle II. The activeness of teacher MAN 3 increased from 75% to 92%; teachers of MA Al Mudatsiriyah increased from 63% to 83%, and teachers of Central Jakarta MA increased from 54% to 79%. This progress has an impact on teacher competence in developing the 2017 revised RPP Curriculum 2013 which has improved from initial condition to cycle I and cycle II. Significant improvement can be seen from 68% in the first cycle, increased to 81% in the second cycle.